Analisis Kebiasaan Belajar Siswa SMP dalam Pembelajaran Daring di Dukuh Gatak Rejo, Drono, Ngawen, Klaten Tahun Pelajaran 2020/2021 - Ardiyani, Nadia Amalia (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2022)
The aims of this study are : 1) to describe learning habits of junior high school’s students in Gatak Rejo, Drono, Ngawen, Klaten, 2) to find out what factors support and hinder students in online learning, 3) to find solutions to online learning problems in order to form students positive learning habits. The research method used is descriptive qualitative. Data collecyion techniques used in this study were observation, interviews and documentation.In data collection, observations werw made by observing the daily life subject, than continued with interviews with the subject, parents and peers, then strengthened by research documentation. The result of this study explain that there is a change in junior high school students learning habits in online learning. Students habits at the beginning of online learning are in the low chategory. In changing students learning habits, it is found that the supporting and inhibiting factors of online learning today are found. Key Words: Habits in online learning